1984
DOI: 10.1149/1.2115999
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence of Ca1 − x Mg x  S  :  A  (  A  = Eu or Ce )

Abstract: Cathodoluminescent properties of Eu2+‐ or Ce3+‐activated normalMgS and Ca1−xMgxS phosphors are investigated at 300 K. It is found that normalMgS:normalEufalse(0.01 normalmole percent false[normalm/normalofalse]false) exhibits a high energy efficiency (∼16 %) and an improved water‐resistance if residual oxide content is less than 1 m/o. Under these highly sulfurizing conditions, normalMgS is confirmed to be completely miscible with normalCaS in any compositional ratio. The composition Ca0.1Mg0.9S:nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…Fig. 6 shows the emission and excitation spectra of Ca 1−x Mg x S:Eu 2+ , Er 3+ phosphor (0 ≤ x ≤ 0.3, CaS and MgS are partially miscible in our experimental condition [24]), their shapes of emission and excitation spectra are similar to Ca 1−x Sr x S:Eu 2+ , Er 3+ . However, we found that the relative intensity of phosphor Ca 1−x Mg x S:Eu 2+ , Er 3+ emission and excitation band increased with increasing of x and achieve the maximum at x = 0.3; on the other hand, the strongest excitation broad-band has a small red shift, which is not beneficial for application in the blue light GaN LED, but this defect is not important compare with its improvement in luminescence intensity; the wavelength of the emission bands have no remarkable changes, which are in agreement with previous report [25].…”
Section: Effect Of Auxiliary Activator Re 3+ On the Fluorescence Intementioning
confidence: 85%
See 1 more Smart Citation
“…Fig. 6 shows the emission and excitation spectra of Ca 1−x Mg x S:Eu 2+ , Er 3+ phosphor (0 ≤ x ≤ 0.3, CaS and MgS are partially miscible in our experimental condition [24]), their shapes of emission and excitation spectra are similar to Ca 1−x Sr x S:Eu 2+ , Er 3+ . However, we found that the relative intensity of phosphor Ca 1−x Mg x S:Eu 2+ , Er 3+ emission and excitation band increased with increasing of x and achieve the maximum at x = 0.3; on the other hand, the strongest excitation broad-band has a small red shift, which is not beneficial for application in the blue light GaN LED, but this defect is not important compare with its improvement in luminescence intensity; the wavelength of the emission bands have no remarkable changes, which are in agreement with previous report [25].…”
Section: Effect Of Auxiliary Activator Re 3+ On the Fluorescence Intementioning
confidence: 85%
“…As mentioned above, the luminescence intensity of red-emitting alkaline earth-based sulfide phosphor was improved but afterglow was not enhanced when Er 3+ was introduced as auxiliary activator. miscible [24]) phosphors with different Sr concentration x, respectively. The excitation spectra of the phosphors conclude two broad bands, at around 260 and 400-600 nm.…”
Section: Effect Of Auxiliary Activator Re 3+ On the Fluorescence Intementioning
confidence: 99%
“…Ce 3 + doped CaS and SrS have been developed as phosphorescent materials for cathodoluminescence and electroluminescence displays [19][20][21]. SrS has a similar structure with CaS where Ce 3 + sits in a six fold Ca 2 + site surrounded by S 2 À ions to make O h symmetry [22].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, rare-earth and transition metal ions doped alkaline earth sulfides (IIa-VIb) have attracted the attention of many researchers and scientists due to their unique applications in photoluminescent devices [1], electroluminescent panels [2], cathode ray tubes [3,4] and thermoluminescent dosimeters [5][6][7]. Energetically favorable defect structure within the photophysical environment of host lattice has captivated the materials engineering community and as a result, recently, the research on doped CaS has gained a fresh impetus due to its possible afterglow features when co-doped with Eu and Ce impurities.…”
Section: Introductionmentioning
confidence: 99%